Community assembly of the ferns of Florida. Issue 3 (5th May 2018) - Sessa, Emily B.; Chambers, Sally M.; Li, Daijiang; Trotta, Lauren; Endara, Lorena; Burleigh, J. Gordon; Baiser, Benjamin
Abstract : Premise of the Study: Many ecological and evolutionary processes shape the assembly of organisms into local communities from a regional pool of species. We analyzed phylogenetic and functional diversity to understand community assembly of the ferns of Florida at two spatial scales. Methods: We built a phylogeny for 125 of the 141 species of ferns in Florida using five chloroplast markers. We calculated mean pairwise dissimilarity (MPD) and mean nearest taxon distance (MNTD) from phylogenetic distances and functional trait data for both spatial scales and compared the results to null models to assess significance. Key Results: Our results for over vs. underdispersion in functional and phylogenetic diversity differed depending on spatial scale and metric considered. At the county scale, MPD revealed evidence for phylogenetic overdispersion, while MNTD revealed phylogenetic and functional underdispersion, and at the conservation area scale, MPD revealed phylogenetic and functional underdispersion while MNTD revealed evidence only of functional underdispersion. Conclusions: Our results are consistent with environmental filtering playing a larger role at the smaller, conservation area scale. The smaller spatial units are likely composed of fewer local habitat types that are selecting for closely related species, with the larger‐scale units more likely to be composed of multiple habitat types that bring together a larger pool of species from across the phylogeny. Several aspects of fern biology, including their unique physiology and water relations and the importance of the independent gametophyte stage of the life cycle, make ferns highly sensitive to local, microhabitat conditions.